Study on Optical-electrical Signal Characteristics of Partial Discharge of Gas-insulated Electric Equipment - Xie, Rui; Ge, Xinyuan; Zhu, Junpeng; Hu, Ripeng; Sun, Zheng (2019 IEEE 3rd International Electrical and Energy Conference (CIEEC), 2019)
On-line monitoring of partial discharge (PD) of gas-insulated electrical equipment has great engineering value. PD detection method that is not subject to any electromagnetic interference has not been found yet. This paper proposes a PD detection method for gas-insulated electrical equipment based on the comparison of UHF method and optical method, which improves the reliability of PD detection. Based on the ability of fluorescent fiber to capture the PD optical signal, the PD detection platform for gas-insulated electrical equipment was built. The four-dimensional typical defect was compared and analyzed. The results show that the UHF signal under different defects has different amplitude, rise time and duration, and the single PD waveform signal obtained by optical method can only reflect the development of PD by amplitude; The UHF signal and optical signal show their respective characteristics in terms of amplitude and phase. Combined with UHF method and optical method, the accuracy of internal defect recognition of GIS can be increased.